The Green Ship - Quentin Blake (London, United Kingdom Random House Children's Publishers UK, 2000)
Two children find the Green Ship when they climb over the wall into what is more like a forest than a garden. The ship has bushes for bows and stern and its funnels are trees; a small garden shed on an ancient stump is the wheel house and in command of the ship is the owner of the garden, old Mrs Tredegar. Throughout the summer she and the Bosun and the two children sail the Seven Seas visiting exotic faraway places and having wonderful adventures.
Keywords: Read Aloud -- Read Aloud